2018
DOI: 10.1016/j.sjbs.2017.03.015
|View full text |Cite
|
Sign up to set email alerts
|

Nano-particle engineered atorvastatin delivery to support mesenchymal stem cell survival in infarcted myocardium

Abstract: Atorvastatin (ATV) may support mesenchymal stem cells (MSC) survival in post-infarct myocardium (MI) as inflammatory reactions, oxidative stress and hypoxia condition get started in such tissues after damage. However, limited aqueous insolubility and rapid first-pass metabolism reduce the systemic availability of ATV. The aim of the present investigation was to develop ATV loaded nanoparticles (ATVNPs) which might ensure the maximum availability of ATV in systemic circulation for longer duration and to strengt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 19 publications
(23 reference statements)
0
7
0
1
Order By: Relevance
“…Strategies aimed at improving aqueous solubility [ 17 , 18 , 19 , 20 , 21 , 22 , 23 ], or prolonging the time on the gastrointestinal tract [ 24 , 25 , 26 ], were gradually replaced by approaches that use the lymphatic system for systemic absorption [ 16 , 27 ]. In fact, some nanoparticles were shown to be able to reach the lymphatic circulation of the intestine (M-cells and Peyer’s patches) [ 28 , 29 , 30 ], thus avoiding the enzymes of the enterocytes and the hepatic first-pass effect [ 16 , 31 ]. Cellulose-based polymers [ 16 ], were found to be superior [ 32 , 33 ], compared to cellulose-free polymers [ 27 , 28 , 29 , 30 ], because they guarantee a sustained release of the drug [ 32 ], due to better mucoadhesive [ 34 ], mechanical [ 35 ] and film-forming [ 35 ] properties and enhanced stability among physiologic pH levels [ 16 , 17 , 32 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Strategies aimed at improving aqueous solubility [ 17 , 18 , 19 , 20 , 21 , 22 , 23 ], or prolonging the time on the gastrointestinal tract [ 24 , 25 , 26 ], were gradually replaced by approaches that use the lymphatic system for systemic absorption [ 16 , 27 ]. In fact, some nanoparticles were shown to be able to reach the lymphatic circulation of the intestine (M-cells and Peyer’s patches) [ 28 , 29 , 30 ], thus avoiding the enzymes of the enterocytes and the hepatic first-pass effect [ 16 , 31 ]. Cellulose-based polymers [ 16 ], were found to be superior [ 32 , 33 ], compared to cellulose-free polymers [ 27 , 28 , 29 , 30 ], because they guarantee a sustained release of the drug [ 32 ], due to better mucoadhesive [ 34 ], mechanical [ 35 ] and film-forming [ 35 ] properties and enhanced stability among physiologic pH levels [ 16 , 17 , 32 ].…”
Section: Resultsmentioning
confidence: 99%
“…In fact, some nanoparticles were shown to be able to reach the lymphatic circulation of the intestine (M-cells and Peyer’s patches) [ 28 , 29 , 30 ], thus avoiding the enzymes of the enterocytes and the hepatic first-pass effect [ 16 , 31 ]. Cellulose-based polymers [ 16 ], were found to be superior [ 32 , 33 ], compared to cellulose-free polymers [ 27 , 28 , 29 , 30 ], because they guarantee a sustained release of the drug [ 32 ], due to better mucoadhesive [ 34 ], mechanical [ 35 ] and film-forming [ 35 ] properties and enhanced stability among physiologic pH levels [ 16 , 17 , 32 ]. Among cellulose-free polymers, compounds with poly-oxy-propylene (hydrophobic fraction) and poly-oxy-ethylene (hydrophilic fraction) induced a 4-fold increase in the oral bioavailability of atorvastatin [ 17 ], but the intrinsic variability of the compounds in terms of dimension and composition should be carefully investigated in tailored studies.…”
Section: Resultsmentioning
confidence: 99%
“…Numerous examinations have considered a particular portion of this medication powerful in the treatment of heart assaults, ventricular capacity alteration in myocardial damage, vascular dilatation, a decrease of fiery procedures in patients with heart failure, and lessening the rate of unexpected cardiovascular demise in patients with incessant heart failure. It has indicated the appropriate impact on vascular endothelial tissue and capillary walls in patients with ischaemic heart failure, and has a defensive impact in patients with myocardial localised necrosis [26][27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%
“…But the efficiency of the molecule was largely reduced due to its limited systemic availability caused by its poor insolubility in aqueous environments. To address this limitation, Yao et al developed a nanoparticle-engineered ATV that ensured its maximum systemic availability, for a prolonged period and to support MSC survival in the injury site 68. Long back, Pons et al have reported the long-term culture of MSCs and showed the expression of cellular stress markers such as p16 INK , p21 and p19 ARF .…”
mentioning
confidence: 99%